Rancang Bangun Aplikasi Pendataan Jemaat dan Aktivitas Gerejawi Berbasis Web pada GKJW Jemaat Waru - Lucky Andrean Wahyudi; Dewiyani Sunarto; Tan Amelia (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2018)
Problems faced by East Java Christian Church (GKJW) Church of Waru are no reports information about a church that is accurate enough to the head waitress Daily Assembly Church (PHMJ) as consideration for planning of ecclesial activity. To get the data to monitor active involvement in church and ecclesiastical activity, church congregations to collect data in each area periodically and perform every worship attendance. Unfortunately, data collection and recording attendance that do are often not documented and not well managed. As a result, completeness of data and information available so that the activity of the church less searches, as well as reporting changes related to church difficult. Based on these problems we need a web-based system has a database as a means to process, manage, and helps generate reports required by the head of the Church GKJW PHMJ Waru. The results of this thesis is the application of data collection churches and ecclesial activity (PJAG) can perform data management, so that the data generated congregation complete and search, as well as changes in reporting requires a short time. PJAG application can present a valid attendance calculations so that attendance recorded properly and the report generating valid information.